Isolation of Corynebacterium Suis from Boars in Selangor, Malaysia - Bahaman, Abdul Rani; Lee, J. S .Y; Too, H. L. (1984)
A preliminary survey for prevalence of Corynebacterium suis infection in boars was conducted on two pig farms in Selangor. Preputial swabs were streaked onto Neomycin blood agar plates and from the characteristic morphology of the colonies and inactive reactions on most of the diagnostic media, Corynebacterium suis was identified. Four of the 24 preputial swabs from the two farms were positive for Corynebacterium suis.